Aqueous Microlenses for Localized Collection and Enhanced Raman Spectroscopy of Gaseous Molecules. Issue 22 (8th September 2021) - Kim, Yun‐Tae; Kim, Daeik; Park, Sanghwan; Zhexembekova, Anar; Byeon, Mirang; Hong, Tae Eun; Lee, Jongwon; Lee, Chang Young
Abstract: Raman spectroscopy of gaseous molecules has been challenging, requiring complicated experimental procedures and peripheral devices for concentrating the analytes. Here, Raman spectroscopy of gaseous molecules at parts‐per‐billion (ppb) levels is demonstrated using aqueous microlenses of LiCl solution that spontaneously absorb water‐soluble gas molecules from the environment. The lenses are easily formed by filling the microwells of an elastomeric stamp with an aqueous solution of LiCl and stamping onto a substrate. Because LiCl is hygroscopic, the aqueous lenses maintain their liquid states under various ambient conditions. Gaseous molecules in the air dissolve in the aqueous microlens and can be identified based on their Raman fingerprints. Lowering the humidity causes the aqueous lens to transition into a salt crystal, while preserving the dissolved molecules within the crystal and facilitating the long‐term storage and analysis of gaseous analytes. By forming the aqueous microlenses on a surface‐enhanced Raman scattering (SERS) substrate, 800 ppb dimethyl methylphosphonate, a nerve agent simulant, is detected in a collection time of only 5 s. Aqueous microlenses that are responsive to the chemical environment are useful for analyzing various water‐soluble gaseous molecules and therefore have broad implications for healthcare, food safety, and environmental‐monitoring applications. Abstract : Highly stable aqueous microlenses composed of hygroscopic salts enable unambiguous identification of various gas‐phase chemical warfare agents based on their Raman fingerprints. Gaseous molecules dissolve and concentrate within the lens without any peripheral collection system. Combining a microlens with surface‐enhanced Raman scattering enables detection of a gaseous molecule at the parts‐per‐billion level.